Perancangan Permainan Interaktif Sebagai Alat Untuk Memperkenalkan Dunia Industri Pada Siswa SMA - Vivi Triyanti; Christine Natalia (JURNAL TEKNIK INDUSTRI, 2011)
The research builds an interactive game to help high school students in getting better understanding of Industrial Engineering.. The game is about the flour production company which process are procurement, production and sales, played by a team consisted of four students. After design and construction phases, the game was tried in Tarakanita High school. Using paired t-test for means, it is concluded that there is increasing grade in posttest value. It means after playing the game ,students have better understanding about aspect that are concerned in Industrial  Engineering. Moreover, based on evaluation review, there are good acceptances of the activities